РЕВИЗОРСКАТА ПРОФЕСИЈА ВО МАКЕДОНИЈА И ВО СВЕТОТ (Yearbook - Faculty of Economics, 2018)
The audit is an independent examination of the financial statements of business entities, banks and other organizations and based on that examination, providing independent opinions on the reliability of those statements, in accordance with the requirements of the task before the auditor and in accordance with relevant legal and professional regulation. The audit confirmed the accuracy of claims in the financial statements for the comprehensiveness, accuracy, existence, occurrence, valuation, measurement, rights and obligations and presentation and disclosure. The purpose of the audit is to provide stakeholders evidence about the authenticity of certain information obtained from those entrusted with the assets of the company. The management of the business entity is obliged to create and implement accounting records and to take care of the preparation of financial statements in accordance with generally accepted standards and financial reporting framework. Auditing as a profession has evolved into a modern scientific discipline that is practiced around the world and is continually working on: improvement (upgrading) of international auditing standards, continuing professional development of certified auditors, compliance with the code of ethics of certified auditors and maintaining the dignity of profession.